Kinetics of oxidative degradation of white wines and how they are Affected by selected technological parameters - Ferreira, António César Silva (2011)
The negative effects of oxygen on white wine quality and the various factors which influence it (including temperature, dissolved oxygen, pH, and free SO2) are well documented both at the sensory and compositional levels. What is less defined is the quantitative relationship between these parameters and the kinetics of the development of the negative effects of oxidation. The experiment presented here attempts to generate data which can be used to predictively model the oxidative degradation of white wines. Bottled wines were submitted to extreme conditions (45 °C temperature, O2 saturation) during 3 months witth samples taken every 15 days for both sensorial and chemical analysis (GC-O/FPD/MS, 420 nm). The synergistic effects of increasing temperature and O2 at lower pH are evident, both on the decrease in levels of terpene alcohols and norisoprenoids (which impart floral aromas), and on the development of off-flavors such as “honey-like”, “boiled-potato”, and “farmfeed” associated with the presence of phenylacetaldehyde, methional, and 1,1,6-trimethyl-1,2- dihydronaphthalene.